2018
DOI: 10.1200/cci.18.00004
|View full text |Cite
|
Sign up to set email alerts
|

Applying Radiomics to Predict Pathology of Postchemotherapy Retroperitoneal Nodal Masses in Germ Cell Tumors

Abstract: PurposeAfter chemotherapy, approximately 50% of patients with metastatic testicular germ cell tumors (GCTs) who undergo retroperitoneal lymph node dissections (RPNLDs) for residual masses have fibrosis. Radiomics uses image processing techniques to extract quantitative textures/features from regions of interest (ROIs) to train a classifier that predicts outcomes. We hypothesized that radiomics would identify patients with a high likelihood of fibrosis who may avoid RPLND.Patients and MethodsPatients with GCT w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…34,35 In addition, there is data supporting the use of this technology as a predictive biomarker in breast cancer, esophageal carcinoma, germ-cell tumors, nasopharyngeal carcinoma and rectal cancer, with discriminative accuracies greater than 70%. 9,10,14,[36][37][38] To date, computer-based image analysis has not been shown to out-perform validated clinical prediction tools, in settings whereby such tools exist; however, their combination with clinical predictors have been shown to improve discriminative accuracy. 36 The utility of this technology in these early applications underscore the need for further study, particularly in settings where clinical predictors alone are ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 In addition, there is data supporting the use of this technology as a predictive biomarker in breast cancer, esophageal carcinoma, germ-cell tumors, nasopharyngeal carcinoma and rectal cancer, with discriminative accuracies greater than 70%. 9,10,14,[36][37][38] To date, computer-based image analysis has not been shown to out-perform validated clinical prediction tools, in settings whereby such tools exist; however, their combination with clinical predictors have been shown to improve discriminative accuracy. 36 The utility of this technology in these early applications underscore the need for further study, particularly in settings where clinical predictors alone are ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,14,[36][37][38] To date, computer-based image analysis has not been shown to out-perform validated clinical prediction tools, in settings whereby such tools exist; however, their combination with clinical predictors have been shown to improve discriminative accuracy. 36 The utility of this technology in these early applications underscore the need for further study, particularly in settings where clinical predictors alone are ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics may help find potentially valuable information through the high-throughput extraction of quantitative features (14, 15). The newly proposed radiomics method has been successfully applied to various diseases (17, 18, 2730). In a recent study, Lewin et al applied radiomics to predict the pathology of postchemotherapy retroperitoneal nodal masses in germ cell tumors (27).…”
Section: Discussionmentioning
confidence: 99%
“…The newly proposed radiomics method has been successfully applied to various diseases (17, 18, 2730). In a recent study, Lewin et al applied radiomics to predict the pathology of postchemotherapy retroperitoneal nodal masses in germ cell tumors (27). Their results showed that the discriminative accuracy, sensitivity, and specificity of radiomics to identify GCT/teratoma vs. fibrosis was 72, 56.2, and 81.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a lot of enthusiasm in the GCT community for joint efforts to build up integrated clinical and biomarkers models for the identification of teratoma and benign residual disease in patients with non-seminoma presenting with postchemotherapy residual disease. In this setting, radiomics has showed promising results and need to be further explored (74,75).…”
Section: Future Prospectivementioning
confidence: 99%